(untitled) (Journal of the Management Sciences, 2024)
Due to issues with corporate transparency in Nigeria, the Securities and Exchange Commission decided to include disclosure and transparency in its code of governance framework in 2018 in line with global best practices to improve investors’ confidence and help resuscitate declining firm value due to lack of investors’ confidence that results from lack of detailed information. Hence, the study examined the effect of corporate transparency among public listed non-financial firms with specific focus on financial, governance, operational and social transparency. The study population consist of 107 non-financial firms quoted on the Nigeria Exchange Group as of December 31st, 2021 of which 67 were sampled. Secondary data obtained from the companies’ annual reports spanned through 2011 to 2021 and was analysed using panel data regression technique. The findings revealed that financial transparency, operational transparency and social transparency are of positive and significant effect on firm value while governance transparency have negative and insignificant effect on firm value. The study then concluded that regulators of the Nigeria capital market could make it more efficient and attractive for investors by enforcing transparency, which is an important underlying aspect that can affect value of firm and improve its overall market capitalization. It recommended that regulators should insist on more transparency to help investors seeking capital gain assess true financial status of the company and improve the firm value.